Effects of Mental Health Literacy Promoting Program with Social Support for Stress Management among Caregivers of Long-Term Care in the Khon Kaen Municipality - Naowanit, Pranee; Padchasuwan, Natnapa Heebkaew; Sihawong, Krittapart (Journal of Human and Society, Sisaket Rajabhat University, 2024)
Stress is a worldwide major mental health problem, and chronic stress can lead to illness. It affects physical health and, in severe cases, may lead to suicide. This research is a quasi-experimental study aimed at examining the outcomes of a program designed to promote mental health literacy combined with social support and to foster stress management behavior among caregivers of dependent people in Khon Kaen Municipality. The sample group consisted of caregivers for dependent people, divided into two groups: an experimental group and a comparison group, each comprising 30 people. The experimental group received a program to promote mental health literacy along with social support, created by the researcher. The program consisted of lecture activities, watching a video demonstrating stress management practices, and tracking usage at home. The comparison group received normal services from officials for a period of 10 weeks. The collected data were then analyzed to compare differences in mean scores within groups and between the experimental group and the comparison group, utilizing Paired t-test and independent t-test statistics, with the statistical significance level set at 0.05. The results showed that, after the experiment, the experimental group demonstrated significantly higher mean scores in various skills, such as accessing mental health information, cognitive skills for managing stress, mental health communication skills, mental health media literacy skills, decision-making skills to manage stress, self-stress management skills, and stress management practices, compared to both their pre-experiment scores and those of the comparison group (p-value < 0.001). After the experiment, the experimental group exhibited a significantly lower mean stress level than before the experiment (p-value < 0.001) and significantly less stress than the comparison group (p-value < 0.001). Therefore, the program, which promotes mental health literacy along with social support, has the potential to foster stress management behavior among caregivers of dependent people.